2009
DOI: 10.1016/j.aca.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of selenium dietary supplements; formation of S-(methylseleno)cysteine and other selenium compounds

Abstract: a b s t r a c tSpeciation of selenium is of interest because it is both essential and toxic to humans, depending on the species and the amount ingested. Following indications that selenium supplementation could reduce the incidence of some cancers, selenium-enriched yeast and other materials have been commercialized as supplements. Most dramatically however, the SELECT trial that utilized l-selenomethionine as the active supplement was terminated in 2008 and there is much debate regarding both the planning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…Introduction of any new product potentially used to supplement Se requires chemical speciation to assess Se bioavailability. Although most dietary selenium is absorbed efficiently, the retention of organic forms is higher than that of inorganic forms [35][36][37][38]. The high level of Se org found in fruiting bodies of investigated mushrooms indicates that P. eryngii or P. ostreatus grown on substrates supplemented with Se may represent a sufficient bioavailable source of Se.…”
Section: Discussionmentioning
confidence: 92%
“…Introduction of any new product potentially used to supplement Se requires chemical speciation to assess Se bioavailability. Although most dietary selenium is absorbed efficiently, the retention of organic forms is higher than that of inorganic forms [35][36][37][38]. The high level of Se org found in fruiting bodies of investigated mushrooms indicates that P. eryngii or P. ostreatus grown on substrates supplemented with Se may represent a sufficient bioavailable source of Se.…”
Section: Discussionmentioning
confidence: 92%
“…In 25 preparations, Se(IV) and selenium-organic compounds were found; in 15, Se(VI) and selenium-organic compounds were observed; in nine, selenium occurred as both Se(IV) and Se(VI) as well as in inorganic compounds. It should be, however, be noted that, in terms of potential selenium bioavailability, the occurrence of inorganic compounds is less favorable than selenium-organic compounds (Amoako et al 2009). In other studies of selenium dietary supplements, the authors found both inorganic forms Se(IV) and, predominantly, Se(VI), as well as selenium-organic compounds, mainly as selenomethionine with traces of selenocysteine (Hsieh & Jiang, 2013).…”
Section: Determination Of Inorganic Selenium Contentmentioning
confidence: 98%
“…In this study, the selenium content in organic compounds was determined without determining the particular organic forms: selenomethionine Se-O, S-(methylseleno)cysteine, selenomethionine (Amoako et al, 2009). In view of contradictory opinion on the significance of particular selenium-organic compounds (selenomethionine versus Se-(methyl)selenocysteine) in cancer prevention (Infante et al, 2004), determination of total selenium-organic compounds allows for assessment of general bioactive properties.…”
Section: Determination Of Selenium Content In Organic Compoundsmentioning
confidence: 99%
“…In all dietary supplement products, selenium was present mainly in the form of organic species (Amoako et al 2009;Alzate et al 2007;Infante et al 2005;Dumont et al 2005). In two samples (samples 1 and 5), no inorganic selenium species were detected.…”
Section: Analysis Of Dietary Supplementsmentioning
confidence: 99%